Labor supply of educated married women in Malaysia and its association with child care arrangements / Suhaida Mohd Amin - Suhaida , Mohd Amin (2016)
The statistics shows that Malaysia has produced more women graduates than men and those women with tertiary education constitute the highest rate of labor participation compared to women with lower levels of education. However, the labor force participation rate (LFPR) among women in Malaysia has remained low for four decades compared to the rest of the ASEAN countries and it is below the global average. In fact, a deeper analysis revealed that the participation rate among educated women in the labor force participation had actually decreased. The most cited reason for women to choose to withdraw or stay out of the market had been due to work-family conflict, especially concerning the issue of child care arrangement. The government, through various efforts, has tried to ensure that the needs of working or to-be working mothers are fulfilled. Recognizing the important role of women in the economy, this study examined the factors associated with the participation of educated married women in the Malaysian labor market. For those with children, child care arrangement associated with the employment status of educated mothers had been explored. Through the application of sequential explanatory mixed method approach to achieve the research objectives, this research was carried out based on a combined framework with the Theory of the Allocation of Time, as the dominant framework having partial common ground with the Theory of Investment in Human Capital and Theory of Access. Additionally, responses from 593 educated married women (Model 1) collected via online survey were analyzed by using Binary Logistic Regression. Examination on the factors that affected their choice whether to participate in the labor market revealed that their decisions were influenced by economic, socio-demographic, and family factors. Furthermore, educated mothers with children less than six years old were found more likely to be not working (Model 2). For that reason, the importance of child care arrangement was further explored through an in-depth interview with nine educated married women who were drawn from the respondents of the quantitative survey. Concerns of parents about the safety of children in child care had been the main reason for them to choose not to work and an interview with three experts in the field confirmed this finding. This study expands the scope of the Theory of allocation of time in that it argues that the over-riding constraint related to child care arrangement must first be overcome, and if and only if, time permits, will women then choose to participate in the labor market. Consequently, although they are educated, women will not necessarily work in the labor market, as highlighted in the Theory of Investment in Human Capital. Providing affordable and quality child care centers, is a way to increase participation. Better quality nurseries should be established in order to guarantee the safety of children, as well as to give more attention to the physical, intellectual, and emotional aspects of children. Thus, mother-friendly working policy needs to be more comprehensive to all women employees in Malaysia; not just to civil servants alone.